Limits and possibilities of the Critical Enviromental Education: alook to the environmental licensing - Mônica do Nascimento Brito; Ana Maria Dantas Soares; Geraldo Márcio Timóteo (Universidade Estadual de Alagoas, 2021)
There is a need for a greater uderstanding of the relationships that are imbricated in Public Environmental Management (PEM), having as principle the Critical Enviromental Education, like an instrument of Federal Environmental Licensing of oil and gas (O&G), serving traditional fishing communities into vulnerable socio-environmental conditions. In this sense, the text's objective is discuss the purposes of Critical Environmental Education in O&G Environmental Licensing, based on Environmental Education Program Pescarte actions in the community of Farol de São Thomé -Campos dos Goytacazes (RJ). Literature review, questionnairies application and participant's observation were adopted as methodological procedures. The study showed the importance of participation in the role of shellfish-gatherers women in decision making and occupation of arenas of power